Snapshots Quiz. Issue 12 (31st August 2021) - Ebrahim, M
Abstract : A 37-year-old, previously healthy, man presented with profuse rectal bleeding necessitating transfusion. Colonoscopy and oesophagogastroduodenoscopy were normal. CT angiography was performed. What is the diagnosis?